YouTube as a learning modality for clinical procedures among medical and dental students: a study in public sector teaching institutes - Shah, Hina; Ahmed, Sanaa; Ayaz, Sumbul; Gul, Amna; Fatima, Urooj; Abbas, Mohammad Taha (Journal of the Pakistan Medical Association, 2024)
Objectives: To evaluate the effectiveness and analyse the influence of YouTube as a learning modality for clinical procedures among medical and dental students in a public-sector setting. Method: The cross-sectional study was conducted at the medical and dental constituent institutes of Jinnah Sindh Medical University and Jinnah Postgraduate Medical Centre between August and October 2023, and comprised undergraduate, graduate, and postgraduate students of either gender aged 18-40 years. Data was collected using a self-administered, structured, closed-ended 16-item questionnaire, which was developed in the English language and explored the usage of YouTube as a source of information about medical and dental clinical procedures. Data was coded and analysed using SPSS 26. Results: Of the 314 participants, 153(48.7%) were medical students and 161(51.3%) were from the dental stream, 175(55.7%) were females, and 139(44.3%) were males. YouTube was a helpful tool for 143(45.5%) students who used it when needed, 172(54.8%) used it occasionally before attempting procedures, while majority of the dental students 140(44.6%) used it to study for prosthodontics. There were 154(49%) students who supported the idea that faculty should recommend watching relevant videos on YouTube, while 256(81.5%) preferred other websites. Conclusion: YouTube was mostly used for learning clinical procedures by the students. Key Words: Computer-assisted instruction, Deep learning, Communication, Oral surgical procedures, Education, Dental.